Molecular evolution of a central region containing B cell epitopes in the gene encoding the p67 sporozoite antigen within a field population of Theileria parva - Obara, Isaiah; Ulrike, S.; Musoke, A.J.; Spooner, P.R.; Jabbar, A.; Odongo, D.; Kemp, Stephen J.; Silva, Joana C.; Bishop, Richard P. (Springer, 2015)
Protective immunity induced by the infective sporozoite stage of Theileria parva indicates a potential role for antibodies directed against conserved serologically reactive regions of the major sporozoite surface antigen p67 in vaccination to control the parasite. We have examined the allelic variation and determined the extent of B cell epitope polymorphism of the gene encoding p67 among field isolates originating from cattle exposed to infected ticks in the Marula area of the rift valley in central Kenya where the African cape buffalo (Syncerus caffer) and cattle co-graze. In the first of two closely juxtaposed epitope sequences in the central region of the p67 protein, an in-frame deletion of a seven-amino acid segment results in a truncation that was observed in parasites derived from cattle that co-grazed with buffalo. In contrast, the variation in the second epitope was primarily due to nonsynonymous substitutions, resulting in relatively low overall amino acid conservation in this segment of the protein. We also observed polymorphism in the region of the protein adjacent to the two defined epitopes, but this was not sufficient to provide statistically significant evidence for positive selection. The data indicates that B cell epitopes previously identified within the p67 gene are polymorphic within the Marula field isolates. Given the complete sequence identity of the p67gene in all previously characterized T. parva isolates that are transmissible between cattle by ticks, the diversity observed in p67 from the Marula isolates in combination with the clinical reaction of the infected cattle is consistent with them originating from ticks that had acquired T. parva from buffalo.